Nontrivial Solutions of a Class of Kirchhoff Type Problems via Local Linking Method - Anmin Mao; Lin Zhang (Abstract and Applied Analysis)
The existence of nontrivial solutions of Kirchhoff type problems is proved by using the local linking method, and the new results do not require classical compactness conditions.